Effect of Wet–Dry Cycles on the Shear Behavior of Compressed Wood Nails Compared to Steel Nails - Fan, Wei; Zhu, Xinrui; Hu, Xinyu; Liu, Hongguang (Forests, 2025)
The corrosion-induced strength degradation of steel nails poses a critical challenge to the structural integrity of timber connection joints, particularly in hygrothermal environments. Compressed wood nails exhibit hygroscopic expansion characteristics, demonstrating their potential as a sustainable alternative to steel nails in structural connections. However, systematic investigations on their shear performance under cyclic hygrothermal conditions remain limited. This study comparatively analyzed the shear behavior evolution of compressed wood nail and galvanized steel nail connections under wet-dry cycles. Distinct failure mechanisms were observed: wood nail connections exhibited characteristic brittle fracture patterns, whereas steel nail connections demonstrated ductile failure through pull-out deformation with nail bending. Notably, compressed wood nails displayed superior environmental stability, with significantly lower degradation rates in terms of load-bearing capacity (2.8% vs. 22.3%) and stiffness (16.3% vs. 38.0%) than their steel counterparts under identical hygrothermal exposure. These findings provide critical design references and data support for implementing wood-based fasteners in moisture-prone engineering applications.